2023
DOI: 10.3389/fpubh.2022.1094036
|View full text |Cite
|
Sign up to set email alerts
|

Does the built environment of settlements affect our sentiments? A multi-level and non-linear analysis of Xiamen, China, using social media data

Abstract: IntroductionHumans spend most of their time in settlements, and the built environment of settlements may affect the residents' sentiments. Research in this field is interdisciplinary, integrating urban planning and public health. However, it has been limited by the difficulty of quantifying subjective sentiments and the small sample size.MethodsThis study uses 147,613 Weibo text check-ins in Xiamen from 2017 to quantify residents' sentiments in 1,096 neighborhoods in the city. A multilevel regression model and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 89 publications
0
3
1
Order By: Relevance
“…Previous studies have suggested a negative correlation between living density and residents' mental health, and the perceived living environment plays a role in residents' mental health [2][3][4]10,11,15]. Although the correlation between objective living space and mental health was not significant in this study, there was a negative correlation between subjective living space and mental health.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Previous studies have suggested a negative correlation between living density and residents' mental health, and the perceived living environment plays a role in residents' mental health [2][3][4]10,11,15]. Although the correlation between objective living space and mental health was not significant in this study, there was a negative correlation between subjective living space and mental health.…”
Section: Discussioncontrasting
confidence: 78%
“…Research has shown that people have basic requirements for physical space [2] and that living in crowded and unfavorable urban environments can significantly impact people's mental health [1,3]. Those who reside in areas with high population density and poor living conditions tend to experience more negative sentiments compared to those who live in less crowded and more favorable environments [4]. This phenomenon is not limited to urban areas alone, as rural residents can be affected as well.…”
Section: Introductionmentioning
confidence: 99%
“…Spatiotemporal analysis of public emotions by using LBSN data has become a popular research topic in urban research and has yielded notable achievements across various aspects. Examples include the relationship between the built environment and public emotions ( Fan et al, 2023 ), the effect of public green space on public emotions ( Chen S. et al, 2022 ), and the opinions of people on public transportation through Twitter data ( Das and Zubaidi, 2023 ). In addition, previous studies used traditional global regression models, such as ordinary least squares (OLS) to explore the relationship between the built environment and public emotions.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods rely too much on surveys, interviews, and questionnaires and have disadvantages such as being time-consuming, having a limited sample size, being too subjective, and being difficult to replicate (Rahnema et al, 2019). Questionnaires and interviews may not accurately reflect a subject's psychological state due to potential biases introduced by the questions and questionnaire design (Fan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%